2021
DOI: 10.3847/1538-4357/ac0d03
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Grid of 2D Kilonova Emission Models

Abstract: Depending upon the properties of their compact remnants and the physics included in the models, simulations of neutron star mergers can produce a broad range of ejecta properties. The characteristics of this ejecta, in turn, define the kilonova emission. To explore the effect of ejecta properties, we present a grid of two-component 2D axisymmetric kilonova simulations that vary mass, velocity, morphology, and composition. The masses and velocities of each component vary, respectively, from 0.001 to 0.1 M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 61 publications
1
52
1
Order By: Relevance
“…In this paper, we adopt an AT2017gfo-like model as our standard kilonova model to calculate the kilonova detectability of serendipitous and GW-triggered ToO observations. However, many theoretical works in the literature (e.g., Kasen et al 2013Kasen et al , 2017Kawaguchi et al 2020Kawaguchi et al , 2021Darbha & Kasen 2020;Korobkin et al 2021;Wollaeger et al 2021) show that BNS kilonova should be diverse which may depend on the mass ratio of binary and the nature of the merger remnant. The possible energy injection from the merger remnant, e.g., due to spindown of a post-merger magnetar (Yu et al 2013(Yu et al , 2018Metzger & Piro 2014;Ai et al 2018;Li et al 2018;Ren et al 2019) 3 or fall-back accretion onto the post-merger BH (Rosswog 2007;Ma et al 2018) could significantly increase the brightness of the kilonova.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this paper, we adopt an AT2017gfo-like model as our standard kilonova model to calculate the kilonova detectability of serendipitous and GW-triggered ToO observations. However, many theoretical works in the literature (e.g., Kasen et al 2013Kasen et al , 2017Kawaguchi et al 2020Kawaguchi et al , 2021Darbha & Kasen 2020;Korobkin et al 2021;Wollaeger et al 2021) show that BNS kilonova should be diverse which may depend on the mass ratio of binary and the nature of the merger remnant. The possible energy injection from the merger remnant, e.g., due to spindown of a post-merger magnetar (Yu et al 2013(Yu et al , 2018Metzger & Piro 2014;Ai et al 2018;Li et al 2018;Ren et al 2019) 3 or fall-back accretion onto the post-merger BH (Rosswog 2007;Ma et al 2018) could significantly increase the brightness of the kilonova.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…the kilonova brightness may have a wide range of distribution and hence confirmed that kilonova emission should be diverse (Gompertz et al 2018;Ascenzi et al 2019;Rossi et al 2020;Rastinejad et al 2021). However, on one hand, kilonova emission is predicted to be highly viewing-angle-dependent (e.g., Kasen et al 2015;Martin et al 2015;Wollaeger et al 2018Wollaeger et al , 2021Barbieri et al 2019;Bulla 2019;Darbha & Kasen 2020;Zhu et al 2020;Korobkin et al 2021) so that one can only observe these kilonova candidates in sGRB afterglows when the line of sight is close to the jet axis. On the other hand, due to the scarce and ambiguous observational data, it is hard to use these limited data to model lightcurves of cosmological kilonovae 4 .…”
Section: Kilonova Emissionmentioning
confidence: 87%
“…Various types of parametrized, axisymmetric ejecta configurations have been employed in a series of papers by the Los Alamos group (Wollaeger et al 2018;Korobkin et al 2021;Wollaeger et al 2021, e.g.) using atomic-physics based opacities (Fontes et al 2020) and two different choices for the composition (Even et al 2020).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%